Damage as premise for compensatory liability - Kulik, Teresa Bernadetta; Kowalska, Agnieszka; Pacian, Anna; Pacian, Jolanta (Polish Journal of Public Health, 2009)
The aim of the paper is to discuss ‘material’ and ‘nonmaterial’ damages as a condition for civil liability and fi nancial (pecuniary) compensation, arising from inappropriate actions of health-care workers. The concept of ‘damage’ is closely related to medical law and should be considered in the context of such law. Damage may be material (e.g. physical damage to a person or property) or non-material damage (e.g. mental suffering or physical discomfort). When considering compensation due to damages, it is necessary to determine its size and impact in the context of a patient’s natural rights or by comparing the situation in which the patient would exist if not for the improper conduct of health care employee with the situation in which the patient does exist as a result of the improper conduct. The paper identifi es examples of both material and nonmaterial damages, drawing on both Supreme Court jurisdiction and the literature. It also examines various forms of compensation, focusing on the conditions that must arise when either seeking compensation of an appropriate sum of money, or return to the state before the damages occurred. It is noted that fi nancial compensation may be in the form of a single reimbursement of costs incurred by the patient due to injury or to other health disorder. Other forms of fi nancial compensation are also described: single cash benefi t and cash compensation for the infringement of natural rights. In addition, the paper focuses on the conditions related to application for a pension by victims who experienced harm in the course of medical procedures, in connection with poor medical procedures, or in connection with poor performance by medical staff.